Application of stable‐isotope labelling techniques for the detection of active diazotrophs. (15th December 2017) - Angel, Roey; Panhölzl, Christopher; Gabriel, Raphael; Herbold, Craig; Wanek, Wolfgang; Richter, Andreas; Eichorst, Stephanie A.; Woebken, Dagmar
Summary: Investigating active participants in the fixation of dinitrogen gas is vital as N is often a limiting factor for primary production. Biological nitrogen fixation is performed by a diverse guild of bacteria and archaea (diazotrophs), which can be free‐living or symbionts. Free‐living diazotrophs are widely distributed in the environment, yet our knowledge about their identity and ecophysiology is still limited. A major challenge in investigating this guild is inferring activity from genetic data as this process is highly regulated. To address this challenge, we evaluated and improved several 15 N‐based methods for detecting N2 fixation activity (with a focus on soil samples) and studying active diazotrophs. We compared the acetylene reduction assay and the 15 N2 tracer method and demonstrated that the latter is more sensitive in samples with low activity. Additionally, tracing 15 N into microbial RNA provides much higher sensitivity compared to bulk soil analysis. Active soil diazotrophs were identified with a 15 N‐RNA‐SIP approach optimized for environmental samples and benchmarked to 15 N‐DNA‐SIP. Lastly, we investigated the feasibility of using SIP‐Raman microspectroscopy for detecting 15 N‐labelled cells. Taken together, these tools allow identifying and investigating active free‐living diazotrophs in a highly sensitive manner in diverse environments, from bulk to the single‐cell level.